POTENSI TANAMAN KANGKUNG DARAT (Ipomea reptans) DAN BAYAM CABUT (Amaranthus tricolor L.) SEBAGAI HIPERAKUMULATOR LOGAM BERAT TIMBAL (PB) TERHADAP PERTUMBUHAN DAN AKUMULASINYA - retno dwi sisarti; Anis Rosyidah; Indiyah Muwarni (AGRONISMA, 2020)
In Indonesia, the conversion of agricultural land into industrial areas is the initial cause of heavy metal pollution on agricultural land. Lead (Pb) is one of the pollutants at issue because it is toxic. One method that can be used to recover heavy metal pollution in the soil is to use a hyperaccumulator plant called a phytoremediation process. This research was conducted to find out how the growth and accumulation ofÂ kale and spinach to lead stress (Pb) by giving different concentrations of lead. This study uses a randomized block design (RBD) experimental design composed of factorial and consists of 2 factors. The first factor, the type of plant (kale and spinach) The second factor, the concentration of lead heavy metals (Pb) which consists of three levels (0 mg / kg, 200 mg / kg, 400 mg / kg). The research results indicated that administration of lead (Pb) with a concentration of 400 mg / kg had the highest damage and was able to inhibit the growth of kale and spinach plants so that plant growth became stunted.Â